2019
DOI: 10.1002/aah.10058
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of Four Fish Tumors

Abstract: The present study supports the usefulness of ancillary techniques, such as immunohistochemistry, as a valid diagnostic tool in the field of fish oncology. The immunohistochemical patterns observed in four neoplasms on four individual teleosts belonging to different species are described. Cytokeratin, vimentin, actin, S100, calretinin, and Melan-A antibodies were used. Diagnoses of papilloma in a Bream Abramis brama, fibroma in a Sand Steenbras Lithognathus mormyrus, schwannoma in a Crucian Carp Carassius caras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
(36 reference statements)
3
27
0
Order By: Relevance
“…This study was performed on 40 adult striped bass M. saxatilis. General condition and health status of fish were evaluated by an external examination for any signs of abnormalities or infestations (Gaglio et al, 2016;Iaria et al, 2018;; on the basis of this, all fish were considered healthy . Fish, coming from a Sicilian farm, in southern Italy, were bred in a recirculating aquaculture system (RAS) containing 6 tanks (8 m in diameter and 60 m 3 in volume; stock density of 20 Kg -3 ).…”
Section: Experimental Designmentioning
confidence: 99%
“…This study was performed on 40 adult striped bass M. saxatilis. General condition and health status of fish were evaluated by an external examination for any signs of abnormalities or infestations (Gaglio et al, 2016;Iaria et al, 2018;; on the basis of this, all fish were considered healthy . Fish, coming from a Sicilian farm, in southern Italy, were bred in a recirculating aquaculture system (RAS) containing 6 tanks (8 m in diameter and 60 m 3 in volume; stock density of 20 Kg -3 ).…”
Section: Experimental Designmentioning
confidence: 99%
“…While in BT, the melanin cells were dense and evenly distributed, the dendritic branches were numerous and relatively thick, the size was large and the color was darker, and many melanocytes were in the growth phase ( Figure 1A2). Previously, the H&E and Masson Fontana staining were used to observe the microstructure of the cross section of fish skin, and the distribution and enrichment of melanin (Iaria et al, 2019;Liu et al, 2019;Monteiro et al, 2019). Our results by these two staining techniques demonstrated that the skins of two distinct color morphs of C. argus were composed of epidermis, tomb membrane, pigment layer, dermis, subcutaneous tissue, and with obvious boundaries, albeit the epidermisin AT was significantly thin, and the pigment layer tended to degenerate without obvious melanocytes.…”
Section: Histological Observation and Analysis Of Skinmentioning
confidence: 99%
“…Tumours in fish are nowadays ever more studied to understand aetiology and pathogenesis (Iaria et al., 2018, 2020; Marino, Germanà, & Panebianco, 2008; Quaglio et al., 2016). Fish from aquaculture production have a short life span and are unlikely affected by diseases related to senescence, differently from broodstock specimens that have a long life span and are frequently subjected to hormonal stimulation (Bailey, Williams, & Hendricks, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the structure of the tissue and localization, they can be differentiated into lipoma, liposarcoma, osteoma, osteosarcoma, fibroma, fibrosarcoma, leiomyoma and leiomyosarcoma, rhabdomyoma and rhabdomyosarcoma (Kleihues & Cavenee, 2000; Schlumberger & Lucké, 1948; Sirri et al., 2015). Several of these tumours have been found in many fish species (Iaria et al., 2018; Lumsden & Marshall, 2003; Marino, Chiofalo, Mazzullo, & Panebianco, 2011; Marino, Licata, et al, 2016). Nevertheless, differentiating these kinds of tumours can be difficult and should be done on histopathological and immunohistochemical bases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation